Diplommatina boessnecki n. sp. from Nepal (Gastropoda: Diplommatinidae) - Walther, Frank; Hausdorf, Bernhard (Zootaxa, 2020)
Diplommatina Benson, 1849 (Caenogastropoda: Diplommatinidae) is a species-rich genus of terrestrial microsnails with a constriction near the beginning of the last whorl (Kobelt 1902). It includes several hundred species in eastern and southern continental Asia, Japan, Taiwan, Indonesia and the Philippines. Although known for more than a century from the Himalayas and other mountain ranges in India, the first Diplommatina from Nepal were reported not before 1997 (Kuznetsov & Schileyko 1997). A recent revision reported 16 species of the genus from Nepal (Budha et al. 2017).